Neck Proprioception in Chronic Neck Pain Patients with Different Typing Speeds: A Pilot Study - Sri, Nevashini; Ong, Jun Hui; Hii, Everlynn, Y.X. (INTI International University, 2023)
BACKGROUND: Chronic neck pain (CNP) is one of the most common musculoskeletal pains. It limits the daily functional activities up to 11% to 14% of the workers. Patients with CNP suffered from decreased neck proprioception, especially in head-eye coordination. The COVID-19 pandemic accelerated computer usage. A fast- typing speed can be easily achieved if there is good typing skill and head-eye coordination. However, the relationship between neck proprioception and typing speed in patients with CNP remains unclear. This study aimed to investigate neck proprioception among CNP patients with slow and fast typing speeds. METHOD: A total of 15 patients with CNP, aged 22.4±2.44 years old were recruited in this study. Participants with typing speed >45 words per minute (WPM) were recruited into the SLOW group (n=8) and <45WPM into the FAST group (n=7). Neck proprioception was assessed using the joint position error (JPE) test for neck flexion, extension, right and left rotation. Independent t-tests were conducted using SPSS 17.0 software with a significance level of less than 0.05. RESULTS: The SLOW group showed a significantly increased in neck flexion JPE (5.239±2.151 vs 2.913±0.8, p=0.019) compared to the FAST group. However, no significant difference was found in JPE for neck extension (3.695±2.169 vs 3.771±1.754, p=0.941), right rotation (3.498±1.18 vs 3.967±0.758, p=0.372) and left rotation (3.923±1.335 vs 3.237±1.687, p=0.395) in the SLOW group compared to the FAST group. CONCLUSION: Decreased neck proprioception, especially neck flexion, was significantly shown in CNP patients with slow typing speed. Hence, aside from pain management and postural education, neck proprioception and typing speed training should be offered to CNP patients who demonstrated slower typing speeds and have poorer neck proprioception performance.